Pemanfaatan Sampah Buah, Air Cucian Beras dan Kotoran Ayam Sebagai Pupuk Organik Cair - Sefti Purnawati; Tuntas Bagyono; Mohammad Mirza Fauzie (Poltekkes Kemenkes Yogyakarta, 2016)
Waste from various sources is potential to pollute all types of environment, i.e. soil, air and wa-ter. Giwangan fruit and vegetable market produces waste as much as 1-3 trucks every day. The content of Nitrogen, Phosphor and Kalium (NPK) in those fruit and vegetable wastes are 331 ppm, 838,1 ppm, and 268,1 ppm, respectively. Used water from rice washing is primary source of organic matter for plant’s tissues. Fertilizer from chicken manure contains the highest K com-pared with other types of manure fertilizer, i.e. 1,50 %. The purpose of the research was to know the difference in quality of liquid organic fertilizer made from the mixture of fruit waste, rice wash-ing water and chicken manure. There were five composition variations. The type of the research was an experiment applying post-test with control group design. The statistical analysis employ-ed one way anova test and LSD at 95 % level of confidence. The observation of physical conditi-on of the fertilizers comprised of odor and color. Descriptively, the results show that the highest N content was found in the Control, meanwhile for P and K, the highest contents were observed in fertilizer B and the Control. The statistical test concludes that the N and P contents of liquid organic fertilizers obtained from all ingredient compositions are significantly different (the p-values are 0,007 and <0,001, respectively). But, for K contents, the differences are not signify-cant (p-value=0,112). The yielded NPK contents have not yet fulfilled the standard quality of good liquid organic fertilizer. However, among the all compositions the best liquid organic fertili-zer is the Control one, since its N and K contents are the highest.